2022
DOI: 10.3390/ijerph19042036
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method to Establish Sufficiency and Stability in Meta-Analyses: With Application to Fine Particulate Matter Air Pollution and Preterm Birth

Abstract: Fine particulate matter air pollution (PM2.5) is a potential cause of preterm birth. Inconsistent findings from observational studies have motivated researchers to conduct more studies, but some degree of study heterogeneity is inevitable. The consequence of this feedback is a burgeoning research effort that results in marginal gains. The aim of this study was to develop and apply a method to establish the sufficiency and stability of estimates of associations as they have been published over time. Cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…To determine how the pooled estimate and its precision changes over time, studies were ordered by increasing year of publication and then cumulative meta‐analysis was repeatedly undertaken after sequential inclusion of each newly published study over time. A stability threshold was estimated to determine if the aggregate evidence can be considered stable or whether inferences are sensitive to the findings of a new study [32]. If the studies reported multiple estimates, the estimate (OR/RR) with most extensive adjustment were used for a cumulative meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To determine how the pooled estimate and its precision changes over time, studies were ordered by increasing year of publication and then cumulative meta‐analysis was repeatedly undertaken after sequential inclusion of each newly published study over time. A stability threshold was estimated to determine if the aggregate evidence can be considered stable or whether inferences are sensitive to the findings of a new study [32]. If the studies reported multiple estimates, the estimate (OR/RR) with most extensive adjustment were used for a cumulative meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%